Bonding Character and Magnetism at the Interface Between Fe and MoS2 Nanosheets. Issue 13 (26th April 2018) - Mantovan, Roberto; Matveyev, Yuri; Vinai, Giovanni; Martella, Christian; Torelli, Piero; Molle, Alessandro; Zarubin, Sergei; Lebedinskii, Yuri; Zenkevich, Andrei
Abstract : In order to enable the use of the prototypical 2D‐layered MoS2 for spintronics, its integration with ferromagnetic layers is mandatory. By employing interface‐sensitive 57 Fe conversion electron Mössbauer spectroscopy (CEMS), hard X‐ray photoelectron spectroscopy (HAXPES), and transmission electron microscopy (TEM), the chemical, structural, and magnetic properties of the Fe/2D‐MoS2 interface are investigated. CEMS shows that out of the first 1 nm of Fe in direct contact with 2D‐MoS2, about half of the Fe atoms keeps the un‐perturbed Fe local environment, partly in regions where the original 2D‐layered structure of MoS2 is preserved as shown by TEM. The remaining reacting Fe atoms exclusively bond with Mo, with the majority of them being characterized by a ferromagnetic environment and the rest coordinating in a paramagnetic Fe‐Mo configuration. The preferential Fe bonding with Mo is corroborated by HAXPES analysis. The results provide detailed insight into the link between the bonding configuration and the interfacial magnetism at the Fe/2D‐MoS2 heterojunction. Abstract : Insights into the link between the bonding configuration and the interfacial magnetism at the interface between Fe and 2D‐layered MoS2 nanosheets are provided. About half of the Fe atoms keeps an unperturbed local environment, mostly on top of regions where the original 2D‐layered structure of MoS2 is preserved. The remaining Fe atoms exclusively bond with Mo in regions of strong intermix, with the majority of them characterized by ferromagnetic environment.